Total Industrial Safety Culture In Manufacturing Sector - Aziz, Lia Dayana Abdul (Universiti Sains Malaysia, 2019)
Nowadays, industrial accidents at the workplace are increasing from year to year. Many researchers are conducting research on industrial accident problems and found that manufacturing industries were among the industries with high-risk industrial accidents. Hence, the main objective of this research study is to evaluate the perception and the level of awareness of the employees working in the manufacturing sector in Penang Island towards the safety culture that was implemented at their workplace. This research study involved the distribution of 140 safety culture questionnaire to the employees that work in manufacturing industries in Penang Island. However, an amount of 101 respondents were taken as sample for this research study. The safety culture questionnaire was partitioned into seven sections: A. OSH Policy, B. Responsibilities of Top Management, C. OSH Training, D. Employee Involvement and Engagement, E. Communication, F. Work Procedure and G. Hazard and Risk Prevention. The questionnaires that were fully answered by the respondents were analyzed by using SPSS software to obtain the results.